Sugar Recovery from Food Waste via Sub-critical Water Treatment. Issue 3 (2nd April 2020) - Mohd Thani, Nurfatimah; Mustapa Kamal, Siti Mazlina; Sulaiman, Alifdalino; Taip, Farah Saleena; Omar, Rozita; Izhar, Shamsul
ABSTRACT: Large quantities of food are wasted globally. Sugars such as monosaccharides and oligosaccharides are valuable carbohydrate compounds that can be hydrolyzed from food waste, particularly from carbohydrate-rich bakery waste. These sugars can be extracted from the waste as a value-added compound for manufacturing other food products. Sub-critical water treatment is a new and emerging extraction technique that is considered as a green extraction technology. Water at high temperature and pressure can be used to hydrolyze and extract the sugars. This paper reviews (1) the general process for producing sugars from food wastes, (2) recovery of sugar (particularly oligosaccharides) from food waste via sub-critical water treatment, and (3) the potential of bakery waste as the resources of sugar recovery.